Vestibular Dysfunction in Wernicke’s Encephalopathy: Predominant Impairment of the Horizontal Semicircular Canals - Lee, Seung-Han; Kim, Sang-Hoon; Kim, Ji-Min; Tarnutzer, Alexander Andrea (Frontiers in Neurology, 2018)
Background: Wernicke’s encephalopathy, a metabolic disorder due to thiamine deficiency, manifests with various neurological symptoms and signs. It has been known as a cause of vestibular dysfunction. Preliminary reports have proposed predominant involvement of the horizontal semicircular canals. Objective: To better characterize the pattern of vestibular impairment in patients with Wernicke’s encephalopathy using quantitative video head-impulse testing and to review the literature regarding this topic. Method: From January 2014 to December 2016, we retrospectively enrolled five cases of Wernicke’s encephalopathy that received quantitative video-head-impulse testing. We retrieved the clinical features from the medical records and reviewed quantitative head-impulse testing and caloric irrigation. Based on the gain and the number of corrective saccades, the function (normal vs. impaired) of each semicircular canal was rated. In addition, we conducted a Medline and EMBASE search to identify other published cases of Wernicke’s encephalopathy that had received quantitative head-impulse testing. Neuro-otologic and neuro-ophthalmologic findings and vestibular-testing results were extracted. Results: A total of 17 patients (own series=5; published cases=12) aged 54.6±11 years were included. Key neurologic findings were ataxia of stance and gait (13/13, 100%), spontaneous nystagmus (7/14, 50%), gaze-evoked nystagmus (17/17, 100%), positive bedside head-impulse testing for the horizontal canals (16/17, 94%) and memory impairment and mental changes (6/11, 54.5%). Regarding vestibular testing, quantitative head-impulse testing (either video based or search-coil based) documented selective bilateral horizontal canal dysfunction with normal or minimal vertical canal impairment (14/14, 100%). On caloric irrigation, bilateral horizontal canal paresis was noted in most cases (10/11, 91%). Conclusion: In Wernicke's encephalopathy, signs of both peripheral and central vestibular dysfunction (i.e., gaze-evoked nystagmus, ataxia of stance and gait, abnormal head-impulse testing) were common. Selective or predominant impairment of the horizontal semicircular canals seems to be the most common finding of Wernicke's encephalopathy likely related to enhanced vulnerability of the medial vestibular nuclei neurons to thiamine deficiency. Quantitative video-head-impulse testing of all six semicircular canals is therefore a useful tool for the diagnosis and should be applied in all patients with suspected Wernicke's encephalopathy.